Educational Management and Literary Strategies for Preventing Sexual Abuse - Mogboh, Veronica; Iloanwusi, Vitalis (International Journal of Arts, Sciences and Education, 2025)
The persistent threat of sexual abuse in Nigerian secondary schools calls for strategic, context-sensitive prevention models. This study explores how educational management practices can integrate literary texts into school safeguarding strategies to enhance students’ awareness and moral consciousness. Drawing from both empirical data and literary analysis, the study adopted a mixed-methods design. A structured questionnaire was administered to 225 respondents, including principals, vice principals, literature teachers, and JSS3 students across five secondary schools in Enugu State. Descriptive statistics, including mean and standard deviation, were used to analyze responses to three research questions. In addition, thematic analysis was conducted on two prescribed literary texts, Sparkles at Dawn by Nimi Ekere and Shattered Dreams by Nasiru Rabiyatu Ahmed both of which explore child abuse from culturally resonant perspectives. Findings revealed that while literary texts moderately enhanced students’ awareness of sexual abuse (M = 2.57), the strategic utilization of these texts by school administrators and teachers remained limited (M = 2.42). The study further identified a strong agreement (M = 2.64) on the role of educational management in optimizing literature-based prevention. Thematic insights from the texts underscored the irony and complexity of abuse, challenging educators to engage students meaningfully. The paper concludes that integrating literature into safeguarding policies, supported by administrative training and curriculum reform, can offer a sustainable model for child protection. Implications for teacher education and school leadership are discussed, alongside recommendations for policy and practice.